Nicotinamide mononucleotide protects ovarian function and oocyte developmental competence during chemotherapy - Lin Shen; Hemei Li; Xueqi Gong; Hanwang Zhang; Yiqing Zhao (Journal of Ovarian Research)
Abstract Background Cyclophosphamide (CTX)-induced ovarian dysfunction and infertility represent significant concerns for reproductive-age or younger female cancer patients. Although various fertility preservation techniques are currently accessible, there remains a pressing demand for an efficient, non-invasive strategy to protect ovarian function that can be employed concurrently with chemotherapy. Considering the significance of nicotinamide adenine dinucleotide (NAD+) in regulating DNA damage and apoptosis, we aimed to examine the protective effects of nicotinamide mononucleotide (NMN, an NAD+ precursor) on ovarian function against CTX-induced damage. Results Eight-week-old female C57 mice were underwent to a 14-day treatment protocol, receiving either saline, CTX, or CTX combined with NMN supplementation. The protective effects of NMN supplementation during CTX treatment on ovarian reserve, oocyte quality, and developmental competence were evaluated. NMN supplementation during CTX treatment increased NAD+ content in the ovary, improved ovarian reserve, enhanced endocrine function, reduced reactive oxygen species (ROS) levels, alleviated DNA damage, and reduced apoptosis. Furthermore, this supplementation improved the rates of two-cell embryo and blastocyst formation, increased total cell counts, while decreasing ROS levels, DNA damage, and apoptosis in blastocysts. Moreover, the protective mechanisms of NMN may involve key genes such as Banp and Rbm47 in the ovarian tissue, along with serum/glucocorticoid-regulated kinase 1 (Sgk1) in oocytes. Conclusions Collectively, our results highlight the protective effects of NMN against CTX-induced damage to the reproductive function, thus addressing a critical gap in fertility preservation. We present a potential non-invasive strategy that does not interfere with cancer therapy timelines.